Jogos de linguagem em crianças pequenas: contribuições da consciência fonológica - Dias, Rafaela Bisognin (2023)
It is known that speaking Portuguese is a spontaneous process for a child who lives with people who speak the language fluently. Conversely, learning to read and write does not come naturally. In this sense, phonological awareness (PA) is an aspect of metalinguistic awareness that stands out as being extremely relevant to the literacy process. With regard to phonological awareness, Soares (2020) and Morais (2019) present didactic strategies based on language games that should be developed with children still in the early childhood education phase, that is, from the age of 4. In light of this, the present research seek to investigate how language games can contribute to the acquisition of phonological skills in young children. More specifically, it was intended: to describe a synthesis of the historical trajectory of literacy, reading, metalinguistic awareness and phonological awareness in the educational context; to understand the methodological strategies presented by Soares (2020) and Morais (2019) that work the skill of phonological awareness in young children; to investigate the relationships made by children when invited to reflect on words and the reflections made during the application of the didactic sequence. For this purpose, a qualitative study of the participant research type was carried out, based on the proposal of Prodanov and Freitas (2013), in a class of students aged 4 years. The data were obtained through a diagnostic assessment, the application of a didactic sequence, as well as through the records contained in the researcher's logbook and the videos with the recordings of the sessions. The analysis of the data was based on the assumptions of Bardin's content analysis (2011), and the categories of analysis, defined a priori, were called lexical awareness and syllabic awareness. The results show that language games, organized according to the assumptions of Soares (2020) and Morais (2019), favor the development of phonological skills, since children also reflect on words while playing, thus enhancing the literacy process